2019
DOI: 10.1002/bies.201900063
|View full text |Cite
|
Sign up to set email alerts
|

Greater Loss of Female Embryos During Human Pregnancy: A Novel Mechanism

Abstract: Given an equal sex ratio at conception, the excess of human males at birth can only be explained by greater loss of females during pregnancy. It is proposed that the bias against females during human development is the result of a greater degree of genetic and metabolic "differentness" between female embryos and maternal tissues than for similarly aged males, and that successful implantation and placentation represents a threshold dichotomy, where the acceptance threshold shifts depending on maternal condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 137 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…With a reported miscarriage rate of approximately 25% and the larger majority occurring in the first trimester (26), the disproportionate loss of female fetuses results in a significant deficit that persists right through the perinatal period even though proportionately more male fetuses are lost during the third trimester and neonatal period. The reasons for the proportionately excessive female wastage in the first trimester have not been completely elucidated (27). However, its evolutionary purpose may be to ensure that the healthiest females survive to ensure effective reproductive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…With a reported miscarriage rate of approximately 25% and the larger majority occurring in the first trimester (26), the disproportionate loss of female fetuses results in a significant deficit that persists right through the perinatal period even though proportionately more male fetuses are lost during the third trimester and neonatal period. The reasons for the proportionately excessive female wastage in the first trimester have not been completely elucidated (27). However, its evolutionary purpose may be to ensure that the healthiest females survive to ensure effective reproductive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are underway exploring how such sex differences may impact survivability and programmed disease in offspring. 93 Studies have shown that the sex ratio of offspring is particularly sensitive to exposure to fatty acids in pregnancy. In opossums, maternal diets supplemented with sardines resulted in the male-biased sex ratio.…”
Section: Effec T Of Omeg A-6 and Omeg A-3 Fat T Y Acids On Offs Primentioning
confidence: 99%
“…If this occurs early in pregnancy, before recognition of pregnancy, this may appear as though male fetuses were never conceived. Additional studies are underway exploring how such sex differences may impact survivability and programmed disease in offspring …”
Section: Effect Of Omega‐6 and Omega‐3 Fatty Acids On Offspring Sex Rmentioning
confidence: 99%
“…Moreover, recurrent pregnancy loss involves a cascade of physiological reactions as well as the activation of numerous signaling pathways, and the NF-κB (nuclear factor-κB) pathway is a crucial pathway. Although, the NF-κB pathway’s function in different biological processes is debatable; on the one hand, it can promote host defense and other protective cellular responses, while on the other, its activation contributes to inflammatory harm in tissues [ 7 ]. It is not unexpected that the NF-κB pathway impacts mitochondrial function and architecture as the NF-κB pathway serves as a transcription factor of the oxidative stress reaction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%